Given,
The linear pair of equations are:
![\begin{gathered} 4x+2y=-3 \\ 4x-3y=22 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/emb9231p33zv5u4uaqndnj11fpx45o2hj5.png)
Required
The solution of the pairs of equations.
Taking the first equation as,
![\begin{gathered} 4x+2y=-3 \\ 2y=-4x-3 \\ y=-2x-1.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1jdhkiy2fl0okcd1jws05ljahmszuvh3vf.png)
Substituting the value of y in second equation then,
![\begin{gathered} 4x-3y=22 \\ 4x-3(-2x-1.5)=22 \\ 4x+6x+4.5=22 \\ 10x=17.5 \\ x=1.75 \\ x=(7)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7okqaimywdxxhf4f2063wxto4dqeaureaa.png)
Substituting the value of x in first equation,
![\begin{gathered} y=-2x-1.5 \\ y=-2(1.75)-1.5 \\ y=-3.5-1.5 \\ y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d67yetpfvynztly8zodj33a6nogmfrhlw4.png)
Hence, the solution of the system is(7/4, -5).